A beginner's guide to bioluminescence resonance energy transfer (BRET). (2nd December 2019) - Sauvageau, Etienne; Lefrancois, Stephane
Abstract : The Beginner's Guides are an ongoing series of articles in the magazine, each one covering a key technique and offering the scientifically literate but not necessarily expert audience a background briefing on the underlying science of a technique that is (or will be) widely used in molecular bioscience. The series covers a mixture of techniques, including some that are well established amongst a subset of our readership but not necessarily familiar to those in different specialisms. This Beginner's Guide covers bioluminescence resonance energy transfer (BRET).